Nova food classification system: a contribution from Brazilian epidemiology - Maria Laura da Costa Louzada; Kamila Tiemann Gabe (Revista Brasileira de Epidemiologia)
ABSTRACT This essay presents the Nova food classification, a conceptual innovation of Brazilian epidemiology, describing its genesis, the scientific evidence derived from its application, and its implications for public health. Created in 2010, Nova classifies foods into four groups based on the degree of processing: unprocessed or minimally processed foods, processed culinary ingredients, processed foods, and ultra-processed foods. Since its development, several epidemiological studies have demonstrated the negative impacts of high consumption of ultra-processed foods on health, such as associations with various non-communicable diseases, including obesity, diabetes, cardiovascular diseases and mental health outcomes. In Brazil, the consumption of these foods has increased significantly in recent decades, with the caloric share of ultra-processed foods rising from 12.6 to 18.4% between 2002–2003 and 2017–2018, with this increase being more pronounced among more vulnerable socioeconomic groups. Nova underpins the recommendations of the Brazilian Dietary Guidelines and has played a crucial role in informing public policies, such as the update of the National basic food basket and the guidelines of the National School Feeding Program, which aim to limit the access to ultra-processed foods. Finally, the essay addresses the political and scientific challenges, including the need for more experimental studies to strengthen the evidence and the potential of fiscal and marketing regulation strategies that take into account the impact of food processing on health.